Exes and o's - Lea, Amy (Berkley Romance, 2023)
"A romance novel-obsessed social media influencer revisits her exes on her hunt for true love in this romantic comedy. Romance book connoisseur Tara Chen has had her heart broken ten times by ten different men-all of whom dumped her because of her "stage-five clinger" tendencies. Nevertheless, Tara is determined to find The One. The only problem? Classic meet-cutes are dead, thanks to modern dating apps. So Tara decides to revisit her exes in hopes of securing her very own trope-worthy second-chance romance. Boston firefighter Trevor Metcalfe will be the first to rush into a burning building but the last to rush into a relationship. Love just isn't his thing. When his new roommate Tara enlists him to help her reconnect with her exes, he reluctantly agrees. But Tara's journey is leading him to discover his own new chapter. The more time they spend together, the more Tara realizes Trevor seems to be the only one who appreciates her authentic, dramatic self. To claim their happily ever after, can Tara and Trevor read between the lines of their growing connection?"--